1997
DOI: 10.1002/bbpc.19971010116
|View full text |Cite
|
Sign up to set email alerts
|

Density Measurements for Expanded Fluid Selenium up to the Liquid‐vapour Supercritical Region by the X‐Ray Absorption Method

Abstract: Density of expanded fluid selenium was measured in the temperature and pressure ranges up to 1650°C and 700 bar including the liquid‐vapour critical point by the x‐ray absorption method. For the measurements, a new type of cell made of polycrystalline sapphire and a high‐pressure vessel of authors' own design were developed. The critical temperature, pressure and density of 1615 ± 5°C, 385 ± 5bar, 1.85 ± 0.03g cm−3, respectively, were obtained. We found that isochores bend in the semiconductor‐metal transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…At 1273 K, the SðQÞ values start to increase and a broad peak at 0.13 Å À1 appears. With increasing temperature, the maximum around 0.13 Å À1 becomes large and the peak position shifts slightly to smaller Q values, while the SðQÞ values at Q min also increase, along with an increase in the Sð0Þ values deduced from the thermodynamic quantities (Hosokawa et al, 1997). Coulet et al (2003) have measured SAXS patterns of fluid Se in the same temperature and pressure range and concluded that the density contrast between the semiconducting and metallic domains was too small to detect using SAXS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 1273 K, the SðQÞ values start to increase and a broad peak at 0.13 Å À1 appears. With increasing temperature, the maximum around 0.13 Å À1 becomes large and the peak position shifts slightly to smaller Q values, while the SðQÞ values at Q min also increase, along with an increase in the Sð0Þ values deduced from the thermodynamic quantities (Hosokawa et al, 1997). Coulet et al (2003) have measured SAXS patterns of fluid Se in the same temperature and pressure range and concluded that the density contrast between the semiconducting and metallic domains was too small to detect using SAXS.…”
Section: Resultsmentioning
confidence: 99%
“…The thin broken line denotes the saturated vapor pressure curve and the open circle is the liquid-vapor critical point. The critical temperature, pressure and density of fluid Se are T C = 1888 K, P C = 38.5 MPa and C = 1.85 g cm À3 , respectively (Hosokawa et al, 1997). The thin solid lines in Fig.…”
Section: Introductionmentioning
confidence: 92%
“…Many experimental studies on the SC-M transition in expanded fluid Se have been carried out and they are cited in the literature [4]. As a distinct behavior accompanying the SC-M transition, the isochors start to bend at temperatures above 1373 K and pressures above 400 bar [1] near a contour of constant dc conductivity of 30 X cm À1 [4]. The bending of the isochors was considered to be the onset of a transition to a densely packed structure with defects such as threefold coordinated centers in the branched chain as assumed by Cabane and Friedel [5].…”
Section: Introductionmentioning
confidence: 98%
“…It experiences a semiconductor-metal-insulator (SC-M-I) transition in an expanded fluid state around the critical point (the critical constants of Se [1]: T c = 1888 K , p c = 385 bar, q c = 1.85 g cm À3 ). The first indication of the SC-M transition in fluid Se was found in the electrical conductivity data by Hoshino et al [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The chain length becomes shorter with increasing temperature and pressure. Near the critical point (T C ¼ 1615 C, P C ¼ 385 bar, C ¼ 1:85 g/cm 3 ), 14) the average chain length is only about 10 atoms long. 11) Fluid Se undergoes a semiconductor-metal-insulator transition when it changes from liquid to vapor continuously with decreasing density over the critical point.…”
Section: Introductionmentioning
confidence: 99%